The haunting of Cassie Palmer - Alcock, Vivien (Great Britain Methuen Children's Books, 1980)
Thirteen-year-old Cassie, the seventh child of a seventh child, begins to exhibit the gift of second sight which enables her to communicate with the Other World.
Keywords: Ghosts -- Fiction; Clairvoyance -- Fiction; England -- Fiction